PENGEMBANGAN MEDIA PEMBELAJARAN EDUCARD (EDUCATION UNO CARD) PADA PEMBELAJARAN PKN DI SDN 13 TILAMUTA, GORONTALO - Ismail, Apriani; Pomalingo, Samsi; Nurainun, Nurainun (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to develop the EDUCARD (Education Uno Card) learning media that meets the criteria of feasibility, practicality, and effectiveness in Civic Education (PKn) to improve student learning outcomes on the meaning and values of Pancasila in grade IV at SDN 13 Tilamuta. This research is a development study using the ADDIE development research model, which includes the stages of analysis, design, development, implementation, and evaluation. The feasibility of the EDUCARD media was tested through validation by a team of experts. The validation results indicate that this media received an average percentage of 96.80%, categorized as very feasible for use by teachers and students in elementary schools. To test practicality, the researcher used a teacher observation sheet, which showed a total score of 39 out of a maximum score of 40, with an average practicality percentage reaching 97.5%, falling into the very practical category. In terms of effectiveness, the application of the media in grade IV at SDN 13 Tilamuta was measured through pretest and posttest scores. The results showed that the average pretest score of 42.27% increased to 83.63% in the posttest, with a difference of improvement of 48.2%. The effectiveness level of the EDUCARD media, based on calculations, reached 70.40%, indicating that the EDUCARD media is categorized as effective. Based on these results, the EDUCARD media has been proven effective in improving student learning outcomes and is suitable for use in elementary school learning.